Stilling the Storm: Worship and Congregational Leadership in Difficult Times - Smith, Kathleen S. (Rowman & Littlefield Publishers, 2006)
When congregations go through difficult times, worship will both reflect and influence those difficulties. The practice of worship itself can be a key part of the congregation's healing process. Teacher and consultant Kathleen Smith successfully demonstrates this truth in Stilling the Storm, a book for anyone seeking a deeper understanding of the ways that worship intertwines with the life and health of a congregations. There are three main types of difficulty congregations can face: times of crisis, transition, and conflict. Smith considers their differences, similarities, and implications for worship, and explains the congregational dynamics that accompany such times and the roles that leaders play. She reviews basic principles of worship and the ways that unique moments and regular habits of worship shape the congregation. For each type of difficulty she suggests important themes for congregations and their worship planners. Smith explores the wide range of liturgical resources available for congregations going through difficult times and how those resources can best be shaped to fit the specific situation they are experiencing. A perceptive guide to the worship we offer to God in all times and situation, Stilling the Storm is an important resource for all congregations of all worship traditions.